PATH-01. MOLECULAR PROFILING OF PAEDIATRIC CENTRAL NERVOUS SYSTEM TUMOURS IN AUSTRALASIA – AN UPDATE ON THE AIM BRAIN AND MNP2.0 PROJECTS. (4th December 2020) - Algar, Elizabeth; Christine, White; Kinross, Kathryn; Buntine, Molly; Jones, David; Pfister, Stefan; Strong, Robyn; Gottardo, Nicholas; Hansford, Jordan
Abstract: The Access to Innovative Molecular Profiling for Paediatric Brain Cancers (AIM BRAIN) project is a trial testing the feasibility of clinical implementation of diagnostic methylation and molecular profiling for central nervous system (CNS) tumours in Australia and New Zealand. AIM BRAIN builds on an existing study, MNP2.0, and allows cross-validation of results derived from identical samples in separate laboratories in Melbourne, Australia, and DKFZ, Heidelberg, Germany. Parallel methylation profiling (Illumina 850K EPIC array) from co-enrolled cases has revealed excellent concordance between laboratories with 50/51 cases (98%) yielding identical classification using the DKFZ Molecular Neuropathology 2.0 Classifier v11b4. 77/91 (85%) of AIM BRAIN cases classified concordantly by methylation array when compared to their diagnostic histopathology. Of these 77 cases, 16 had classifications below a threshold of 0.90, however still classified correctly. In 14 discordant cases either the histopathology was not well defined, not represented on the classifier, or a very low classification score was obtained. Molecular profiling through MNP2.0 identified 49/167 (29.3%) tumours with gene fusions including BRAF-KIAA1549 (n=29), RELA - C1lorf95 (n=5) and 15 rare or novel fusions. BRAF-KIAA1549 was almost exclusively associated with pilocytic astrocytoma (28/29) and RELA- C1lorf95 with ependymoma. Six pathogenic germline mutations were identified in TP53 (n=2), BRCA1, NF1, LZTR1 and ATM . The incidence of germline predisposition was low (4%) and sex biased towards females (5F:1M), (p<0.08). Our findings confirm methylation profiling as a robust platform for classifying CNS tumours with potential to reveal new CNS tumour entities when combined with molecular profiling.